Implementasi Strategi Perkembangan Sistem Ekonomi Berbasis Pancasila di Era Modern - Yusuf Hamdani; Arisa Oktaviana Maharani; Supriyono Supriyono (FKIP, Universitas Palangka Raya, 2026)
The birth of the modern era brings positive and negative influences so that nations that are unable to utilize it properly will experience economic inequality in society. There are negative economic influences whose implementation is not based on Pancasila, resulting in low resistance to external influences that prioritize material needs and give rise to greed. This happens because it has not fully implemented the values of Pancasila into the national economy in the modern era. Economic improvement in the modern era is increasingly important to improve people's welfare. Efforts to improve the economy must be fair and prioritize the interests of society, so that everyone can enjoy it. To build harmony in improving the Indonesian economy, it is necessary to implement an economic system development strategy based on Pancasila. Pancasila economics is a concept of thinking about planning in the implementation of the national economy within a framework based on the implementation of the values contained in the Pancasila paradigm. The method we use is qualitative. The aim of developing economic growth is to produce broad employment opportunities without inequality.